2003
DOI: 10.1073/pnas.1034823100
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, neurochemical, and electrophysiological characterization of a genetic mouse model of depression

Abstract: Depression is a multifactorial illness and genetic factors play a role in its etiology. The understanding of its physiopathology relies on the availability of experimental models potentially mimicking the disease. Here we describe a model built up by selective breeding of mice with strikingly different responses in the tail suspension test, a stress paradigm aimed at screening potential antidepressants. Indeed, ''helpless'' mice are essentially immobile in the tail suspension test, as well as the Porsolt force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
173
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 239 publications
(189 citation statements)
references
References 34 publications
13
173
2
1
Order By: Relevance
“…For all other experiments, data were collected from females only. Indeed, previous studies showed that differences between H and NH mice (regarding notably adaptive behavioural and neurobiological responses to chronic treatment with antidepressants) were larger in females than in males (El Yacoubi et al, 2003).…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…For all other experiments, data were collected from females only. Indeed, previous studies showed that differences between H and NH mice (regarding notably adaptive behavioural and neurobiological responses to chronic treatment with antidepressants) were larger in females than in males (El Yacoubi et al, 2003).…”
Section: Methodsmentioning
confidence: 98%
“…All mice used for these studies were of the H and NH lines (CD1 strain), selected across 12-14 generations for high or low spontaneous 'helplessness' in the tail suspension test, as described previously (El Yacoubi et al, 2003). For the study of spontaneous sleep-wakefulness patterns, both males and females were used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations